Biopsy of Brainstem Gliomas Using Flexible Endoscopes - Torres-Corzo, Jaime Gerardo; Sanchez-Rodriguez, Jose; Castillo-Rueda, Juan Lucino; Falcon-Escobedo, Reynaldo; Cervantes, Dominic; Rodriguez-Della Vecchia, Roberto; Vinas-Rios, Juan Manuel (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Objectives To describe our experience and the results obtained in performing transventricular brainstem biopsy with the use of flexible neuroendoscops.Methods We identified patients who underwent a neuroendoscopic procedure with brainstem lesion biopsy to obtain histopathologic diagnosis and to treat obstructive hydrocephalus. All patients had follow-up examinations at months 1, 3, 6, and 12 postsurgery and then annually.Results Seven patients had a transventricular biopsy of the brainstem performed. Of those, five were pediatric patients. The median age was 10 years (range: 3–26 years). Five of them were female and two male. Four patients presented with secondary obstructive hydrocephalus. The main clinical presentations were intracranial hypertension syndrome in four patients, motor neuron disease in four patients, two with decreased state of alertness, two with gait ataxia, and one with Parinaud syndrome. The types of tumors found in the histopathology and their location were one ventral (pons) and one aqueductal anaplastic astrocytoma, two ventral, one aqueductal, and one attached to the floor of the fourth ventricle pilocytic astrocytoma and one ventral low-grade astrocytoma. The route taken to approach the ventral tumors was made through premammillary fenestration. The tumors of the aqueduct and floor of the fourth ventricle were approached transaqueductally.Conclusion The use of flexible endoscops for biopsy of ventral, dorsal (tectum lamina quadrigemina), and diffuse brainstem tumors is a useful, effective, and safe procedure that also allows to treat obstructive hydrocephalus secondary to the tumors.
Keywords: biopsy; brainstem glioma; hydrocephalus; neuroendoscopy